Implementation of TPACK-Based Arabic Language Learning in Class VIII at SMPI-PK Muhamadiyyah Delanggu - Rofiq, Muhammad; Firdausi, Muthi'ah Zahrotul; Hasan, Moh. Abdul Khaliq (Global Education Journal, 2025)
Learning activities do not solely occur through interactions between teachers and students, but also through the relationship between students and the media used in the learning process. This study aims to analyze the application of the Technological Pedagogical and Content Knowledge (TPACK) framework in Arabic language learning in grade VIII of SMPI-PK Muhammadiyah Delanggu, and to identify the advantages and challenges of its implementation. This research method uses a qualitative-descriptive method. Data were collected through observation, interviews, and documentation techniques. The results show that teachers have systematically integrated TPACK through the planning, implementation, and evaluation stages. Commonly used learning media are LCD/PPT projectors, videos, and audiovisuals, but the use of interactivity-based media (such as Kahoot and Quizizz) and computer laboratory facilities is still not optimal. The advantages found from the implementation of TPACK are increased student understanding of the material and strengthening teachers' technological competencies. However, this study also identified several obstacles, namely the limited ability of teachers to develop media, minimal supporting facilities, and low technological literacy of some students. These findings conclude that strengthening technology-based Arabic language learning requires continuous improvement of digital teacher capacity and optimization of school facilities and infrastructure.